Marruecos y los marroquíes en la propaganda oficial del Protectorado (1912-1956) - Eloy Martín Corrales (Mélanges de la Casa de Velázquez)
The Spanish authorities in the Protectorate promoted an idealised image of Morocco by means of the iconography through which the colony was depicted in national and international exhibitions and in tourist promotion (posters, stamps, postcards, etc.). Pride of place was given to idealised portrayals of traditional ways of life (craftsmen, merchants, idlers, farmers, shepherds, fishermen, etc.), all set in a peaceful, industrious and well-groomed atmosphere that reeked of paternalism. In this traditional image it was perforce necessary to include –albeit in tiny doses– graphic examples of the modernisation introduced by the « protecting » nation: aeroplanes, motor cars, boats, trains, factories, bridges, roads, modern schools and so forth. Nevertheless, the resulting image, respectful if paternalistic of the colonised people, existed side by side with the negative perception of Moroccans that the orientalists and the colonialists had evinced in former times and continued to evince, and with a large proportion of the iconographic output then produced by private initiative.